Captador para ayudas técnicas, a partir de señal de EMG, con depuración de accionamientos involuntarios por la hipótesis temporal extendida - Roca Dorda, Joaquín; Villarejo Mañas, José Antonio; Roca González, Joaquín (Revista Mexicana de Ingenieria Biomedica, 2000)
This article summarizes our experiences and results obtained when using surface.EMG potentials for the synthesis of logical switch, alike signals as those used to operate different technical aids designed to grant computer access for motor disabled peoples. In order to filter the undesired switch activation pulses due to involuntary movements, we propose a new variation of the classical time validation algorithm, (which we have previously tested widely) based upon the Extended Temporal Hypothesis, which is introduced here as direct result of the analysis of the EMG signal associated to the Muscles involved with switch activation.